Geographies of education: A journey. Issue 1 (9th February 2021) - Kraftl, Peter; Andrews, William; Beech, Suzanne; Ceresa, Giulia; Holloway, Sarah L.; Johnson, Vicky; White, Catherine
Abstract: This paper provides a critical overview of scholarship on the geographies of education. The article explores some of the key roots, linguistic traditions, and conceptual underpinnings of what has become a burgeoning and diverse area of scholarship. It emphasises the different subdisciplinary areas to which research on geographies of education has contributed, including work on social reproduction, the relationship between education spaces and their "outsides, " the agency of learners, structural inequalities, learners' experiences, materialities, and mobilities. The paper concludes with some suggestions about future work on geographies of education, identifying key areas of potential in terms of connection: with scholarship on geography education; with research going on outside geography; with scholarship on education spaces less well‐represented thus far (such as Further Education); and with research on and from non‐Anglophone contexts and the Majority Global South. Abstract : This paper provides an overview of scholarship on the geographies of education. It considers research from a number of geographical traditions, providing a wide‐ranging review of work on issues as diverse as identities, political ideals, materiality, inequality, mobility, and learners' experiences. The paper also explores potential avenues for future research on geographies of education.